2018
DOI: 10.21608/ejh.2019.25408
|View full text |Cite
|
Sign up to set email alerts
|

Effect of titanium dioxide nanoparticles on the spleen of adult male albino rats: Histological and immunohistochemical study

Abstract: Introduction: Titanium dioxide nanoparticles (TiO 2 NPs) are commonly used in industry (e.g. cosmetics, sunscreens, food products, paints and drugs). But, they have different adverse cellular effects including oxidative stress and cellular damage. Aim of the work: To evaluate the possible toxic effect of titanium dioxide nanoparticles on the structure of the spleen of rats. Materials and Methods: Forty-five adult male rats were divided into three groups. Group I served as the control group. Group II (low-dose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 45 publications
(56 reference statements)
0
4
0
Order By: Relevance
“…Colony forming efficiency [80], flow cytometric techniques [105] and Vialight Plus bioluminescence assay Kit [37] were used in some studies. For apoptosis analysis, techniques like flow cytometry [104,106], using dyes such as Annexin V staining [97,99,[106][107][108], TUNEL assays [60,79,[109][110][111][112], and caspase activity detection kits [76,78,113,114] were applied. The majority of the studies used monocultures of human Caco-2 cells (23/72).…”
Section: Cell Death and Proliferationmentioning
confidence: 99%
See 1 more Smart Citation
“…Colony forming efficiency [80], flow cytometric techniques [105] and Vialight Plus bioluminescence assay Kit [37] were used in some studies. For apoptosis analysis, techniques like flow cytometry [104,106], using dyes such as Annexin V staining [97,99,[106][107][108], TUNEL assays [60,79,[109][110][111][112], and caspase activity detection kits [76,78,113,114] were applied. The majority of the studies used monocultures of human Caco-2 cells (23/72).…”
Section: Cell Death and Proliferationmentioning
confidence: 99%
“…One study using low TiO 2 concentrations (~2 mg/kg/bw) found no significant disturbance of the function or structure of the intestine, liver, spleen, lungs, or testis [139]. After rodent oral exposure to TiO 2 -NPs, inflammatory reactions with tissue morphological or functional changes were observed in several organs, including spleen [36,112], liver [56,58,60,72,77,78,94,140,142,143,148,[157][158][159] (with increased serum glucose and insulin resistance, or fibrosis and increased serum levels of liver enzymes), lung [160,161], kidney [145,151] (altered urea, creatinine and uric acid levels), heart (with changes in heart rate and systolic blood pressure) [144], testis [114,149], brain [150], stomach [146,162], and transfer of TiO 2 -NPs to offspring via breast milk [111].…”
Section: Inflammationmentioning
confidence: 99%
“…On the one hand, this has a positive effect when nanoparticles deliver drugs so that the drug delivery system is better. However, the ease with which small nanoparticles pass through the membrane can cause toxic side effects (3).…”
Section: Effects Of Nanoparticles On the Spleenmentioning
confidence: 99%
“…They have a surface area that fits perfectly into the surface of microbial cells, and they can damage the cell walls and DNA of many microbes (2) . However, nanoparticles are potentially toxic and harmful to living organisms although this depends on the type, size, concentration, solubility, stability, as well as chemical and physical properties of each type of nanoparticles (3) .…”
Section: Introductionmentioning
confidence: 99%